Agroclimatic Determinants of Clove Production in Indonesia - Dudy Nugroho; Anna Fitriani (Universitas Muhammadiyah Palembang, 2026)
Indonesia is the world’s largest producer of clove (Syzygium aromaticum), accounting for approximately 73% of global output, supported by agroclimatic conditions that are highly favorable for clove cultivation. However, climate change, manifested through rising temperatures, increasingly erratic rainfall patterns, and more frequent drought events, has contributed to a decline in national productivity to approximately 260–360 kg ha⁻¹, nearly 50% below its potential yield. This study examines the influence of structural and agroclimatic factors on Indonesia’s clove production and assesses their implications for the country’s comparative advantage. Using a quantitative approach, time-series data from 2002–2023 were analyzed through multiple linear regression. The results reveal that plantation area and annual average temperature exert positive effects on clove production, with coefficients of 0.387 and 66,896, respectively, whereas rainfall does not exhibit a statistically significant partial effect. Nevertheless, the variables jointly have a significant influence on production at the 95% confidence level, as indicated by an F-statistic of 74.544 exceeding the critical value of 3.05 (p < 0.05). These findings demonstrate that Indonesia’s clove production is shaped by the interaction between structural and agroclimatic determinants. Strengthening plantation management, improving climate adaptation measures, and enhancing production resilience are therefore critical to sustaining productivity, preserving export competitiveness, and maintaining Indonesia’s leading position in the global clove market under increasing climate-related pressures